Os efeitos da estrutura de propriedade sobre a política de dividendos da empresa brasileira - Brandão, José Wellington (2014)
Despite contradictory findings, for decades, on the dividend policy, the decision to pay dividends is still a very controversial topic. Several factors have been proposed as capable of explaining the dividend policy, for example, profit / profitability, the prior dividend (maintenance in dividend policy), firm size, leverage and growth opportunities. More recently, the literature has explored the interference that the ownership structure may have on the distribution of dividends. In this context arise propositions of hypotheses related to the use of the dividend policy as an instrument of control of the executive direction, and the possible expropriation of minority shareholders by the controlling. The objective of this research is to evaluate the effects of ownership structure on the dividend policy of the Brazilian company in the theoretical framework of the Theory of Agency and these two hypotheses. The sample is a panel data set consists of a total of 1890 annual observations of 223 firms in the period 1996 to 2012 from data collected in Economática system companies with shares traded on the São Paulo Stock Exchange. From the estimation of a set of explanatory models of dividend policy results indicate that the presence of a controlling shareholder has a negative effect on dividend policy in line with the hypothesis of expropriation. Another important result is the positive effect of the presence of other non-financial company, as a major or principal shareholder, on the level of dividend distribution, which is consistent with the hypothesis monitoring of executive management.